Helicity-Dependent Cross Sections for the Photoproduction of π0 Pairs from Nucleons - Dieterle M. Manuel; Witthauer L. Lilian; Fiks (Fix) A. I. Alexander Ivanovich; Abt S.; Achenbach P. Patrick (2020, 2020)
Title screen